Microbial diversity and potential functional dynamics within the rhizocompartments of Dendrobium huoshanense - Xie, Guijuan; Yin, Zhichao; Zhang, Zhenlin; Wang, Xinyu; Sun, Chuanbo (Frontiers in Plant Science, 2024)
Understanding the microbial diversity and potential functional dynamics within the rhizocompartments of Dendrobium huoshanense is crucial for unraveling the plantmicrobe interactions that influence its medicinal properties. This study is the first to characterize the microbiome associated with the rhizocompartments of Dendrobium huoshanense, including its cultivation medium, rhizosphere, rhizoplane, and root endosphere, using high-throughput sequencing. Bacterial phylogenetic diversity was significantly higher in the endosphere than in the rhizosphere, while fungal α-diversity significantly decreased from the cultivation medium to the endosphere. Both bacterial and fungal niche widths decreased from the cultivation medium to the endosphere, indicating a shift from generalist to specialist microbes. β-diversity analysis revealed distinct spatial patterns in both bacterial and fungal communities across the rhizocompartments, with the most pronounced differences between the cultivation medium and the endosphere. Taxonomically, Proteobacteria and Ascomycota were predominant in the endosphere for bacterial and fungal communities, respectively.Functional predictions showed significant enrichment of pathways related to xenobiotics biodegradation, lipid metabolism, and nitrogen fixation in the endosphere, while functions associated with plant pathogens and saprotrophs were significantly reduced. This suggests that D. huoshanense strongly selects for endophytic fungi.Interestingly, a high proportion of fungi with unknown functions were found in the endosphere, highlighting an area for further research regarding the medicinal efficacy of D. huoshanense. Overall, this study provides foundational data for understanding the adaptive evolution of these microbial communities in response to specific microhabitats.